2019
DOI: 10.1371/journal.pone.0217171
|View full text |Cite
|
Sign up to set email alerts
|

Farming strategies of 1st millennium CE agro-pastoralists on the southern foothills of the Tianshan Mountains: A geoarchaeological and macrobotanical investigation of the Mohuchahangoukou (MGK) site, Xinjiang, China

Abstract: Archaeological evidence emerging over the past decade clearly illustrates that agro-pastoralists living along the foothills of major mountain chains in Central Asia (the so-called “Inner Asian Mountain Corridor” or IAMC) facilitated the spread of domesticated grains through their direct involvement in farming. While the environmental conditions across the northwestern slopes of the IAMC provided adequate resources for incipient farming and herding as early as the mid-3 rd mill. BCE, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 64 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…(a) Land cover and shaded relief map of each of the sites with published archeobotanical assemblages in the studied area, (b) the percentage of the cropping yield for each site, and (c) the number of different types of seeds found at each site. 1: Tuzusai (Spengler et al, 2013); 2: Begash (Spengler et al, 2014); 3: Tasbas (Spengler et al, 2014); 4: MGK (Li et al, 2019); 5: Yingpan (Chen et al, 2016); 6: Xiaohe (Yang et al, 2014); 7: Gumugou (Zhang et al, 2017); 8: Xintala (Zhao et al, 2013); 9: Yuergou (Jiang et al, 2013); 10: Shichengzi; 11: Shirenzigou (Tian et al, 2018a); 12: Gudongtan (Dong et al, 2017); 13: Shaguoliang (Dong et al, 2017); 14: Huoshaogou (Dong et al, 2017); 15: Dadunwan (Dong et al, 2017). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(a) Land cover and shaded relief map of each of the sites with published archeobotanical assemblages in the studied area, (b) the percentage of the cropping yield for each site, and (c) the number of different types of seeds found at each site. 1: Tuzusai (Spengler et al, 2013); 2: Begash (Spengler et al, 2014); 3: Tasbas (Spengler et al, 2014); 4: MGK (Li et al, 2019); 5: Yingpan (Chen et al, 2016); 6: Xiaohe (Yang et al, 2014); 7: Gumugou (Zhang et al, 2017); 8: Xintala (Zhao et al, 2013); 9: Yuergou (Jiang et al, 2013); 10: Shichengzi; 11: Shirenzigou (Tian et al, 2018a); 12: Gudongtan (Dong et al, 2017); 13: Shaguoliang (Dong et al, 2017); 14: Huoshaogou (Dong et al, 2017); 15: Dadunwan (Dong et al, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…Recent research reveals that the indigenous agro-pastoralists likely practiced food production strategies different than the Han dynasty towns in the Tarim basin. Li et al’s (2017, 2019) recent investigations in the Yanqi basin at the Mohuchahangoukou (MGK) site, dated to 1st millennium AD, reveals that in the Yanqi basin agro-pastoralist settlements relied on smaller, less labor-intensive irrigation networks that were likely only seasonally occupied. Li et al’s (2019) analysis of carbonized plant remains at MGK found bread wheat, barley, common millet, and foxtail millet, suggesting that the indigenous people adopted a more flexible farming strategy than that seen at Milan.…”
Section: Food Production Strategies On the Western Frontier Of The Hamentioning
confidence: 99%
See 1 more Smart Citation
“…3), Gumugou (Zhang et al, 2017) (Figure 1 No. 4) and Loulan (Li et al, 2019) (Figure 1 No.18). This may indicate simpler riparian forest communities in the Tarim Basin however it is noted that only the Xiaohe Cemetery in the Tarim area was subject to systematic archaeobotanical research.…”
Section: Resultsmentioning
confidence: 98%
“…Increasingly, research on the Central Asian highlands has focused on multi-directional, interand intra-regional connections. As early as the Bronze Age (third to second millennium BC), the Inner Asian Mountain Corridor-a piedmont zone spanning the Hindu Kush to the Altai Mountains-facilitated the movement of crops and other commodities across Eurasia (Frachetti 2012); in turn, these plants and goods were integrated into the economies of pastoralist groups (Spengler et al 2014;Li et al 2019). Recent archaeological investigations focusing on the medieval period (eighth to thirteenth century AD) reveal that upland regions of Central Asia were socio-political mosaics, shaped by communication and commerce across extensive Silk Route networks (Franklin 2016).…”
Section: Background and Rationalementioning
confidence: 99%